The Risky Side of Leadership: Conceptualizing Risk Perceptions in Informal Leadership and Investigating the Effects of Their Over-Time Changes in Teams - Zhang, Chen; Nahrgang, Jennifer D.; Ashford, Susan J.; DeRue, D. Scott (Organization Science, 2020)
Despite the common portrait of leadership as a worthy, needed, and frequently rewarded endeavor, individuals do not always step up to lead as informal leaders in their teams. In the present research, we introduce the idea of leadership risk perceptions, arguing that individuals sometimes see risks for themselves if they step up to lead. We conceptualize three types of leadership risk perceptions (interpersonal, image, and instrumental) and investigate how changes in these risk perceptions over time impact the overall level of informal leadership that individuals contribute in their teams, as well as how these risk perceptions’ change trajectories are shaped by the level of conflict in a team. To address these issues, we conducted a series of studies, exploring the relevance of the three risk perceptions qualitatively, developing measures for them, and then testing our hypotheses in a field study following 454 individuals working in 89 master of business administration (MBA) consulting teams. We found that a decrease in an individual’s leadership risk perceptions over time was related to the individual’s overall informal leadership contributions in the team, though the pattern of relationship was not the same for all three risk perceptions. Furthermore, in teams with higher levels of relationship conflict, interpersonal and image risk perceptions decreased less over time, suggesting the importance of the social context in shaping perceived risks. Overall, this research calls attention to the much under-investigated risky side of leadership and highlights a temporal approach to understanding the impact of leadership risk perceptions.